2001
DOI: 10.1289/ehp.0110971
|View full text |Cite
|
Sign up to set email alerts
|

Applications of gene arrays in environmental toxicology: fingerprints of gene regulation associated with cadmium chloride, benzo(a)pyrene, and trichloroethylene.

Abstract: Toxicity testing of unknown chemicals currently uses a number of short-term bioassays. These tests are costly and time consuming, require large numbers of animals, and generally focus on a single end point. The recent development of DNA arrays provides a potential mechanism for increasing the efficiency of standard toxicity testing through genome-wide assessments of gene regulation. In this study, we used DNA arrays containing 148 genes for xenobiotic metabolizing enzymes, DNA repair enzymes, heat shock protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…In vertebrate, MT gene promoters contain metal (Buhler and Kagi, 1974) and glucocorticoid response elements ( Kelly et al, 1997), and also ARE (Dalton et al, 1994). Previous gene arrays studies with cadmium chloride but not benzo[a]pyrene nor ticholoroethylene induced high expression of MT-1 and MT-II as well as several heat shock/stress response genes and early response genes (Bartosiewicz et al, 2000(Bartosiewicz et al, , 2001. However, for SUL, the latter genes were not found to be modulated.…”
Section: Discussionmentioning
confidence: 95%
“…In vertebrate, MT gene promoters contain metal (Buhler and Kagi, 1974) and glucocorticoid response elements ( Kelly et al, 1997), and also ARE (Dalton et al, 1994). Previous gene arrays studies with cadmium chloride but not benzo[a]pyrene nor ticholoroethylene induced high expression of MT-1 and MT-II as well as several heat shock/stress response genes and early response genes (Bartosiewicz et al, 2000(Bartosiewicz et al, , 2001. However, for SUL, the latter genes were not found to be modulated.…”
Section: Discussionmentioning
confidence: 95%
“…As mentioned previously, it has been reported that carcinogenic metals including Cd and Ni exhibited different patterns of gene expressions and had different carcinogenic mechanisms [Bartosiewicz et al, 2001;Andrew et al, 2003]. Hence, the gene alterations that were considered to be associated with carcinogenesis have not been shown directly.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, some DNA microarray analyses have been performed with animal tissues and cultured cells exposed to metals, and the specific gene expression patterns have been compared with the ones obtained after exposure to the known carcinogenic chemicals. Bartosiewicz et al [2001] have shown that cadmium chroride, Benzo[a]pyrene, and trichloroethylene exhibited different patterns of gene expression in the livers of exposed mice. Likewise, Andrew et al [2003] reported that cadmium chloride, sodium dichromate, and nickel subsulfide altered only a few genes that overlapped with DNA-cross-linker mitomycin C in human lung cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although many environmental xenobiotics induce the synthesis of Hsps, some like benzo(a)pyrene, a ubiquitous environmental pollutant and a potent procarcinogen and mutagen that can elicit tumors, inhibits their synthesis. This points to the special toxicity of these xenobiotics and at potential mechanisms of diseases caused by this chemical (Bartosiewicz et al 2001;Gao et al 2004).…”
Section: Introductionmentioning
confidence: 99%